Furthering the understanding of product formation in monoethanolamine degradation: A mechanistic DFT study. (September 2022) - Parks, Christopher; Hughes, Kevin J.; Pourkashanian, Mohammed
Highlights: DFT studies on oxidative and thermal degradation of monoethanolamine were performed. Mechanistic pathways were modelled and interpreted with respect to experimental conditions. Pathways modelled here provide a basis for future chemical kinetic models. Abstract: A thorough understanding of the product formation originating during degradation of monoethanolamine is crucial to future commercialization of carbon capture plants. Here we report on a series of density functional theory (DFT) calculations outlining chemical pathways for the formation of oxidative degradation products. Fragmentation of monoethanolamine (MEA) radicals is surmountable given standard experimental conditions and can lead to the formation of ethanal, ethanoic acid, ammonia, methylamine, water, formaldehyde, formic acid and imines. Alternatively, the MEA radicals can form hydroperoxides after reaction with oxygen which can subsequently go on to form glycine, glycolic acid and N-(2-hydroxyethyl)glycine (HEGly). Experimentally surmountable routes to the formation of oxazoline, N-(2-hydroxethyl)ethylenediamine (HEEDA), N, N'-bis(2-hydroxyethyl)ethylenediamine (BHEEDA), epoxides, (2-Methylamino)ethanol (MAE), N-(2-hydroxyethyl)imidazole (HEI) and diethanolamine (DEA) are also presented. Graphical Abstract: Image, graphical abstract